Older adults' involvement in developing satisfactory pasta sauces with healthy ingredients. Issue 4 (3rd April 2018) - Predieri, Stefano; Sotis, Gianluca; Rodinò, Paola; Gatti, Edoardo; Magli, Massimiliano; Rossi, Federica; Daniele, Giulia Maria; Cianciabella, Marta; Volpe, Roberto
Abstract : Purpose: The third age can be a period of major food consumption changes. Either voluntary or imposed by health issues, they may be accompanied by alterations in sensory acuity. The purpose of this paper is to investigate how lifelong food habits and health-age issues affect food choice at a later age, with the aim of developing strategies to direct aged people toward healthier food habits. Design/methodology/approach: A survey, aimed to investigate differences between current and past food habits, was carried out in a group of 170 Italian older adults. Questions focused on the composition of the main meal, asking participants to describe its actual structure and to highlight differences in previous years' food habits. A discrete choice experiment (DCE) was planned, during which participants were asked to help formulating innovative pasta sauces with healthy ingredients. Findings: This survey clearly illustrated gender-related differences: women were characterized by a higher consumption of vegetables, while men revealed a more frequent use of wine, pasta and meat. The DCE technique suited older adults' abilities and enabled the development of innovative sauces, indicating a clear preference for extra virgin olive oil, as compared to cream or butter. Gender-related differences were confirmed: women mainly chose a vegetarian sauce, while men expressed an inclination for red meat. Originality/value: This is the first report of a successful application of the DCE technique to investigate older adults' dietary choices. The outspoken preference for olive oil as fat in sauce composition is a positive finding for future actions aimed at directing older adults toward healthier food habits.